Оброблена кістка та ріг із Тіри-Білгорода римського та ранньомодерного часу (матеріали розкопок 2020—2021 рр.) - Савельєв, О.К.; Грицюта, О.О.; Сєкерська, О.П. (Археологія, 2023)
У статті опубліковано кістяні та рогові вироби, знайдені під час археологічних досліджень
у Тірі-Білгороді в 2020—2021 роках. Матеріали походять із шарів і комплексів римської та
ранньомодерної епох. Виокремлено побутові
вироби, предмети для ігор, предмети озброєння, знаряддя праці, облицювальні пластини, заготовки та відходи виробництва. In 2020—2021, during excavations in the Civil Courtyard of the Akkerman Fortress, a collection of 26 bone items was collected,
which are being published in the following article. The objects come from the layers and complexes mainly of the Modern
(16th — 18th centuries) and Roman times and according to their functional purpose belong to several categories. The household
items and the items for games (buckle fragments of knife handles, hookah mouthpieces, gambling or divination astragals, and a
button), weapon products (rings for pulling back the bowstring), and work tools, facing plates, blanks and production waste are
singled out.
Items made of bone and horns are one of the main categories of material for the reconstruction of various aspects of the
economy, everyday life and spiritual life of the ancient population. The analysed bone and horn objects are a small part of the
collection of bone artefacts from the Tyras-Bilhorod excavations of the antique and modern periods, but they provide insight into
the production of specialised crafts and manufacturing of bone products in individual households. Despite the small number of
finds, the collection includes such categories of material as raw materials, blanks, production waste and finished items, which is
one of the signs of the bone-cutting production presence directly on the territory of the city.
Characterising the raw material base of the bone-cutting production, we should point out that the material for manufacturing
was bones and horns of animals that were bred or obtained by the inhabitants of the city — a horse, a domestic bull, a sheep,
a European deer and roe deer, as well as bone rays of the pectoral fins of sturgeon. During production, the peculiarities of the
structure of bone raw materials were taken into account, which made it possible to use the shape of the bone/horn the best possible
way to manufacture a specific object/tool. Certain types of bone objects existed in a rather wide chronological range (astragals
for the game, plates — covers of knife handles etc.) The obtained results are important for the reconstruction of the bone-cutting
and complement the existing ideas about the daily life of the inhabitants of Tyras-Bilhorod in the Roman and Modern times.